Bleeding from breast tumor as a medical emergency - Colakovic, Natasa; Petričević, Simona (Halo 194 Scientific Journal of Emergency Medicine, 2023)
Introduction: Breast cancer is the most common malignant disease in women. It affects about one million women in the world every year, with a continuous incidence increase. Thanks to advances in diagnostics, the introduction of screening, surgical and oncological treatment, breast cancer nowadays is a well-controlled disease, and often completely curable. However, we still encounter locally advanced forms of this malignancy in clinical practice. A frequent complication of such ulcerated tumors is bleeding, which represents a life-threatening emergency and in most cases must be resolved by palliative surgical intervention. Methodology: The PubMed database and GoogleScholar were searched and relevant articles were found according to specific keywords.Conclusion: Recognition of bleeding as a complication and adequate surgical treatment lead to prolongation of survival and quality of life improvement, even when dealing with a patient in the terminal stage of a malignant disease.
Keywords: emergency; breast cancer; bleeding